Balancing Act : Finding Equilibrium Between Work and Life - Patterson, Joan Gurvis. Gordon (Center for Creative Leadership, 2005)
Balance isn't an issue of time but of choice. It's about living your values by aligning your behavior with what you believe is really important. Achieving such alignment is much like any other developmental experience: the basic process involves assessment, challenge, and support.